THE INCIDENCE OF ANEMIA IN TERMS OF GESTATIONAL AGE AND HISTORY OF CHRONIC ENERGY DEFICIENCY IN PREGNANT WOMEN - Anggrawati Wulandari (Universitas STRADA Indonesia, 2022)
Background:Anemia is a condition with hemoglobin levels below 11 gr/dl in pregnant women I and III or levels <10.5 gr/dl in the II trimester. The purpose of this study was to analyze the relationship between the incidence of anemia in terms of gestational age and Chronic Energy Deficiency in pregnant women at the Central Sulawesi.Method:The research design used in this study is correlational analytic with a cross sectional time approach.The sampling method in this study uses accidental sampling techniques.Results:The analysis test using Chi Square shows that the significance level is 0.000 < = 0.05. Thus, there is a relationship between gestational age and Chronic Energy Deficiency in pregnant women with the incidence of anemia at the Siniu Public Health Center.Conclution: It was concluded that gestational age and Chronic Energy Deficiency can cause anemia in pregnant women at the Siniu Health Center, Motong Regency, Central Sulawesi.Keywords:Anemia, Gestational Age, Chronic Energy Deficiency